Semi-Analytical Integration of the Accelerogram and Equations of Motion of a System Subjected to a Paraseismic Shock - WALENTYŃSKI Ryszard (Architecture, Civil Engineering, Environment)
The task of analysing shocks in areas of paraseismic mining activities is one of the important engineering tasks. Acceleration measurements should be integrated to receive velocity and displacement functions. Sometimes, numerical algorithms produce wrong results. This paper proposes a semi-analytical approach to this problem. The algorithm has been implemented within the Mathematica system. Moreover, this method has been applied to integration of the equation of motion.